2006
DOI: 10.1152/physiolgenomics.00201.2005
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome kinetics of arsenic-induced adaptive response in zebrafish liver

Abstract: -Arsenic is a prominent environmental toxicant and carcinogen; however, its molecular mechanism of toxicity and carcinogenicity remains poorly understood. In this study, we performed microarray-based expression profiling on liver of zebrafish exposed to 15 parts/million (ppm) arsenic [As(V)] for 8 -96 h to identify global transcriptional changes and biological networks involved in arsenic-induced adaptive responses in vivo. We found that there was an increase of transcriptional activity associated with metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 64 publications
2
61
0
Order By: Relevance
“…Protein degradation is predominantly mediated by the proteasomes but can also take place in lysosomes, especially during turnover of membrane proteins (Clague & Urbé, 2010). An increased turnover of arsenic-bound proteins is in agreement with the evidence of the catabolism of arsenic-induced improperly folded or damaged proteins via the ubiquitindependent protein degradation pathway in zebrafish liver (Lam et al, 2006). Several studies report that protein ubiquitination not only targets protein degradation using the proteasome pathway but also the lysosomal pathway (Marques et al, 2004;Barriere et al;, Shenoy et al, 2008Arancibia-Cárcamo et al, 2009).…”
Section: Discussionsupporting
confidence: 81%
“…Protein degradation is predominantly mediated by the proteasomes but can also take place in lysosomes, especially during turnover of membrane proteins (Clague & Urbé, 2010). An increased turnover of arsenic-bound proteins is in agreement with the evidence of the catabolism of arsenic-induced improperly folded or damaged proteins via the ubiquitindependent protein degradation pathway in zebrafish liver (Lam et al, 2006). Several studies report that protein ubiquitination not only targets protein degradation using the proteasome pathway but also the lysosomal pathway (Marques et al, 2004;Barriere et al;, Shenoy et al, 2008Arancibia-Cárcamo et al, 2009).…”
Section: Discussionsupporting
confidence: 81%
“…It is found ubiquitously in our environment including drinking water, foods, soil, and airborne particles, and there is a generally well-accepted doseresponse relationship between arsenic ingestion and cancer incidence [34,35]. Microarray-based expression profiling of the livers of zebrafish exposed to arsenic revealed global transcriptional changes and suggested that DNA and protein damages due to arsenic metabolism and the arsenic-induced oxidative stress are the major causes of cellular injuries observed in the liver [36]. Many genes encoding proteins in-volved in DNA damage/repair, antioxidant activity, hypoxia induction, iron homeostasis, arsenic metabolism, heat shock proteins, and ubiquitin-dependent protein degradation were found to be differentially expressed [36].…”
Section: Environmental Omics Of Single Chemicals Vs Chemical Mixturementioning
confidence: 99%
“…Microarray-based expression profiling of the livers of zebrafish exposed to arsenic revealed global transcriptional changes and suggested that DNA and protein damages due to arsenic metabolism and the arsenic-induced oxidative stress are the major causes of cellular injuries observed in the liver [36]. Many genes encoding proteins in-volved in DNA damage/repair, antioxidant activity, hypoxia induction, iron homeostasis, arsenic metabolism, heat shock proteins, and ubiquitin-dependent protein degradation were found to be differentially expressed [36]. cDNA microarray and enzyme-linked immunosorbent assays were also used to identify genes involved in arsenic-associated atherosclerosis [37].…”
Section: Environmental Omics Of Single Chemicals Vs Chemical Mixturementioning
confidence: 99%
“…In any case, the hepatic production of GRP75 seems to be especially sensitive to stress, and a recent study evidenced low transcript levels of GRP75 in the liver of gilthead sea bream in comparison to data found in the common dentex (Dentex dentex L.) (Bermejo-Nogales et al, 2007), a stressful fish closely related to gilthead sea bream. Likewise, in vivo toxicogenomic studies indicated that the expression of GRP75 is 2-3 times increased in the liver of zebrafish exposed to arsenic for 8-96 h (Lam et al, 2006). Taken together all these findings, the inducible expression of fish GRP75 could be considered an adaptive response to restore cellular homeostasis in a distorted and oxidative milieu.…”
Section: Discussionmentioning
confidence: 78%
“…The key role of Hsp70 and Hsp90 families on development has been evidenced during zebrafish embryogenesis (Krone et al, 2003), and even it is known that most hepatic Hsp including GRP75 are up-regulated in zebrafish toxicogenomic models (Lam et al, 2006). Extensive studies have also revealed that the production of Hsp is induced by common aquaculture stressors (e.g.…”
Section: Introductionmentioning
confidence: 99%